Clinical evaluation of effectiveness of new product of specialized sports nutrition for correction of psychophysiological state and neuromuscular transmission in highly qualified athletes - E. S. Tokaev; T. A. Pushkina; E. A. Nekrasov; I. S. Krasnova; A. A. Khasanov (National Electronic Information Consortium (NEICON), 2022)
The purpose of the study is to determine the effectiveness of the specialized product Fit Tonus for correcting the psychophysiological state and neuromuscular transmission in highly qualified athletes.Materials and methods: the objects of research were: specialized product of sports nutrition for correcting the psychophysiological state and neuromuscular transmission Fit Tonus; 21 male martial arts athletes aged 14 to 25 years. The researches were carried out in accordance with official and conventional techniques. Body temperature, breathing rate, blood pressure level, heart rate was determined, heart rate variability, ECG, external breathing, O2 intake, total urine test, clinical blood test, biochemical blood indices were evaluated, water sectors of the body, body skinny weight, body fat weight were determined. Full-function cardiopulmonary analysis was performed using the Meta Lyzer 3B inpatient cardio-respiratory loading diagnostic system (Cortex Medical, Germany). Maximum oxygen consumption was determined by a Cosomed metabolograph (Italy). Biochemical parameters (bilirubin, ACT, ALT, urea, uric acid, glucose, cholesterol, HGT, amylase, alkaline phosphatase, creatinine) were examined on a Humalyzer biochemical analyzer. Water sectors of the body, the value of skinny body weight and fat body weight were determined on an analyzer for assessing the balance of water sectors of the body (Medass, Russia).Results: in the analysis of biochemical blood values, the blood levels of indicator enzymes and their isoforms were normalized in a short time, despite high training loads. This fact reflects the adaptation of the athlete's body to high-intensity physical activity when taking the Fit Tone product. The obtained results of the increase in GUS, FFV and Tiffno test indicate an increase in both functional capabilities and functional abilities of the external breathing system, as well as an increase in the efficiency of the respiratory center in athletes who received the tested product. The effectiveness of the test product is confirmed by the results of dynamic and stress samples in a stabilometric study. Results of examination of psychophysical status of single wrestlers showed that during usage of developed product such indicators as performance, vegetative coefficient, dynamism, speed of movement, accuracy of actions, stability of actions are significantly increased. At the same time, the level of fatigue and anxiety is reliably reduced.Conclusions: the results of the researches performed showed that the product developed demonstrated efficacy for most of the parameters under research in the main group compared to the control (placebo).